Approaches to EFL teaching: curriculum, culture, instruction, assessment, & technology 8 - Gabriela Figueroa Arellano (2015)
Teaching English as a foreign language (EFL) requires that instructors of this language keep up to date with the new tendencies in education in order to provide students with meaningful learning opportunities for them to acquire this language successfully. It also demands that EFL teachers have a vast knowledge about the fundamental concepts and theories that surround EFL teaching and learning. These concepts include pedagogical and other conceptions such as curriculum, culture, instruction itself, assessment, and today’s teaching tendency, technology, which frame EFL classes. Knowing about curriculum allows teachers to become aware of the different factors that affect the creation or improvement of the curriculum as well as its components such as lesson planning, taking into account that a good curriculum is the basis for a quality education. Likewise, since many non-English speaking countries are considered multicultural or as in the case of Ecuador, pluricultural, understanding how culture influences learning is necessary in order to provide our students with culture-sensitive classrooms. Other concept that effective EFL instructors should be familiar with is instruction itself. In other words, how we will set our classes on the lesson plan and put what has been planned into practice. It is in this part of our practice where we demonstrate our knowledge about old and current teaching methods and principles as well as our teaching philosophy which reflects how we guide and support EFL students to learn this language successfully. Therefore, it is in this part where we put theory into practice. A well-planned instruction is always accompanied by good assessment practices. Consequently, being informed about how to provide our students with possibilities to demonstrate their knowledge through active and authentic assessments will challenge traditional paper-and-pencil tests practices and turn the evaluation part of our instruction into knowledge flowering. Finally, with the growing use of internet and technology, it is pivotal that EFL teachers start looking for ways to include tech in their classes.